Deferoxamine can prevent pressure ulcers and accelerate healing in aged mice. Issue 3 (25th October 2018) - Bonham, Clark A.; Rodrigues, Melanie; Galvez, Michael; Trotsyuk, Artem; Stern‐Buchbinder, Zachary; Inayathullah, Mohammed; Rajadas, Jayakumar; Gurtner, Geoffrey C.
ABSTRACT: Chronic wounds are a significant medical and economic problem worldwide. Individuals over the age of 65 are particularly vulnerable to pressure ulcers and impaired wound healing. With this demographic growing rapidly, there is a need for effective treatments. We have previously demonstrated that defective hypoxia signaling through destabilization of the master hypoxia‐inducible factor 1α (HIF‐1α) underlies impairments in both aging and diabetic wound healing. To stabilize HIF‐1α, we developed a transdermal delivery system of the Food and Drug Administration–approved small molecule deferoxamine (DFO) and found that transdermal DFO could both prevent and treat ulcers in diabetic mice. Here, we demonstrate that transdermal DFO can similarly prevent pressure ulcers and normalize aged wound healing. Enhanced wound healing by DFO is brought about by stabilization of HIF‐1α and improvements in neovascularization. Transdermal DFO can be rapidly translated into the clinic and may represent a new approach to prevent and treat pressure ulcers in aged patients.